On the isotropy of induced multipole moments in heavy ion complexes. Issue 7 (20th November 2017) - Trumm, Michael
Abstract : Polarization effects have been proven to play an important role in the theoretical description of chemical processes. With this respect, we report ab initio calculations describing multiconfigurational and relativistic effects as well as electron correlation to determine dipole‐ and quadrupole polarizabilities for all trivalent actinide and lanthanide ions. The results are used in an iterative point‐multipole model to compute polarization interaction for different metal compounds. Significant differences between the usage of isotropic polarizabilities for the coordinating ligands compared to the full tensor representation is found. Quadrupole contributions are found to be negligible for symmetric geometries but can contribute up to 30 kJ/mol to the polarization energy in specific cases. The employed method allows a parameter free study of multipole interactions for a wide variety of systems. © 2017 Wiley Periodicals, Inc. Abstract : The multipole expansion of the energy function offers important insights on the electrostatic interaction of a system. Induced dipoles are commonly considered when analyzing classical interactions. This study focuses on the anisotropic part of induced dipoles as well as induced quadrupole interactions in trivalent lanthanide and actinide complexes.